Performative Skepticism: Pseudoscientific Dogmatism Under the Veil of Rhetorical Doubt - Demambre Bacchi, André (Philosophy and Realistic Reflection, 2025)
This essay explores the concept of "performative skepticism," a rhetorical strategy that mimics the language and principles of scientific skepticism, but is employed to shield beliefs and practices from rigorous empirical scrutiny. Unlike legitimate epistemic skepticism, a foundational component of scientific inquiry, performative skepticism exploits the appearance of critical inquiry to undermine evidence-based knowledge, particularly in the field of health. The analysis begins with a philosophical examination of skepticism, tracing its evolution from Cartesian doubt to the critical methodologies of Popper, Kuhn, and Feyerabend. It then distinguishes performative skepticism from legitimate skepticism, highlighting its asymmetric application of critical standards and reliance on the rhetorical appropriation of scientific language. This essay further examines how performative skepticism manifests in health practices, including anti-vaccine movements, alternative therapies, and digital misinformation. These cases illustrate how performative skepticism distorts scientific values, presenting unsubstantiated claims as though they were scientifically valid. Finally, this essay proposes criteria for distinguishing between legitimate skepticism and performative skepticism, emphasizing the need for proportionate scrutiny and methodological transparency. Understanding and countering performative skepticism are essential for preserving the integrity of science and protecting patients from unfounded interventions.